2021
DOI: 10.1038/s41598-021-87075-4
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width as a novel prognostic marker after myocardial revascularization or cardiac valve surgery

Abstract: The red blood cell distribution width (RDW) measures the variability in the size of circulating erythrocytes. Previous studies suggested a powerful correlation between RDW obtained from a standard complete blood count and cardiovascular diseases in both primary and secondary cardiovascular prevention. The current study aimed to evaluate the prognostic role of RDW in patients undergoing cardiac rehabilitation after myocardial revascularization and/or cardiac valve surgery. The study included 1.031 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In recent years, RDW has been found to be a predictor of multiple adverse health outcomes unrelated to anemia, including increased risk for death from cardiovascular disease [6][7][8][9][10][11][12], SARS-CoV-2 [13][14][15], sepsis [16,17], lung disease [18], and cancer [19,20]. Like all cell membranes, RBC membranes are a complex lipid bilayer [21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, RDW has been found to be a predictor of multiple adverse health outcomes unrelated to anemia, including increased risk for death from cardiovascular disease [6][7][8][9][10][11][12], SARS-CoV-2 [13][14][15], sepsis [16,17], lung disease [18], and cancer [19,20]. Like all cell membranes, RBC membranes are a complex lipid bilayer [21].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Lazzeroni et al reported the potential of RDW to represent an independent predictor after myocardial revascularization or cardiac valve surgery. 34 Akin et al and Zhao et al found that RDW was associated with the development of CA-AKI in patients with ST-segment elevation myocardial infarction and stable angina pectoris. 35,36 In accordance with previous studies, this study demonstrated that high RDW was an independent risk factor of CA-AKI in all patients after CAG or PCI, indicating that enhanced surveillance of RDW might help to identify CA-AKI earlier.…”
Section: Discussionmentioning
confidence: 98%
“…In another study that determined the prognostic value of the RDW, the authors reported an increased mortality rate among patients with above-normal RDWs [22].…”
Section: Discussionmentioning
confidence: 99%
“…After comparing lipid values across RDW categories adjusted for age, hemoglobin level, and MCV, the RDW was found to be negatively associated with HDL-C levels and positively associated with the atherogenic index of plasma, triglyceride levels, and total cholesterol-to-HDL ratio in women [ 21 ]. In another study that determined the prognostic value of the RDW, the authors reported an increased mortality rate among patients with above-normal RDWs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%